A reading test and its role in the teaching and learning processes - Nunes, Myriam Brito Corrêa (The ESPecialist, 2012)
This paper intends to describe and discuss classroom dialogues about the answers given by the students in reading tests designed to encourage readers to interact with the text. My study concentrates on the interpretation of the power relation between teacher and students and on the interactional procedures in classroom practices. The results of the data analysis emphasize the role of verbal interaction in the process of meaning-making and in the criteria of evaluation since different answers have been accepted as correct depending on the readers’ conceptions, misconceptions as well as their social and cultural background.